Gestational and early postnatal exposure to simulated high altitude does not modify postnatal body mass growth trajectory in the rat - Bozzini, Carlos Eduardo Jose (2014)
Postnatal hypoxia blunts body mass growth. It is also known that the quality of the fetal environment can influence the subsequent adult phenotype. The main purpose of the study was to determine whether gestational hypoxia and early postnatal hypoxia are able to blunt growth when the offspring is raised under normoxia. Hypobaric hypoxia was induced in simulated high altitude (SHA) chambers in which air was maintained at 380 mmHg (5450 m). Mature Sprague-Dawley rats of both sexes were divided in normoxic (NX) and hypoxic (HX) groups and, in the case of the HX group, maintained for 1 month at 5450 m. Mating was then allowed under NX or HX conditions. Offspring were NX-NX, NX-HX, HX-HX, or HX-NX: the first term indicates NX or HX during both gestation and the first 30 days of life; the second term indicates NX or HX during postnatal life between days 30 and 133. Body mass (g) was measured periodically and body mass growth rate (BMGR, g/d) was estimated between days 33 and 65 of postnatal life. Results can be summarized as follows: 1) BM was significantly higher in NX than in HX rats at weaning; 2) BMGR was not significantly different between NX-NX and HX-NX rats, and between HX-HX and NX-HX animals; and 3) BMGR was significantly higher in rats living under NX conditions than in those living under HX conditions during postnatal life. Data suggest that that hypobaric hypoxia during gestational and early postnatal development of rats does not alter the regulation of body mass growth in rats when compared to that seen under sea-level conditions.